Maternal adult attachment and maternal–fetal attachment in the context of romantic relationship quality after premature birth–A cross sectional study - Lutkiewicz, Karolina; Bidzan, Mariola (Frontiers in Psychiatry, 2022)
Objective: The primary outcome of the study was to evaluate the maternal adult attachment and maternal – fetal attachment (MFA) in the context of romantic relationship quality among mothers of preterm born children. Associations between MFA, maternal adult attachment, maternal perceived stress, depressive symptoms, social support in the neonatal period were also examined as secondary outcomes. Methods: The study had a cross-sectional design and involved 260 of women after premature birth, who participated in the study in the early neonatal period. The following self-reported methods were used: Socio-demographic questionnaire, Attachment Styles Questionnaire (ASQ), Maternal – Fetal Attachment Scale (MFAS), The Perceived Stress Questionnaire (PSQ), The Dyadic Adjustment Scale (DAS), The Edinburgh Postnatal Depression Scale (EPDS), The Social Support Questionnaire (SSQ). Results: The results showed that a secure attachment style is associated with a higher intensity of the MFA and consequently, a higher quality of the romantic relationship. Regression analysis presented that the higher the secure attachment score, the lower the perceived level of stress and depressive symptoms, which in turn lead to a higher quality of the partner relationship. Conclusion: Maternal secure attachment positively impacts the romantic relationship quality and the maternal – fetal attachment. The findings also draw attention to the role of the secure attachment style as a protective factor while coping with stress and depressive symptoms.